Pengembangan Lembar Kerja Peserta Didik (LKPD) berbasis Kearifan Lokal Materi Cerita Rakyat SDN 33 Bengkulu Selatan - Leona Rizah; Abdul Muktadir; Puspa Djuwita (Universitas Bengkulu, 2022)
This study aims to (1) describe the development of Learner’s worksheet based on local wisdom material for folklore at SD Negeri 33 Bengkulu Selatan, (2) determine the feasibility of Learner’s worksheet based on local wisdom material for folklore at SD Negeri 33 Bengkulu Selatan, (3) determine the feasibility of Learner’s worksheet based on local wisdom at SD Negeri 33 Bengkulu Selatan. State 33 South Bengkulu. This research is a development research. The method used is R & D by adapting the 6 steps of development from Borg and Gall, namely (1) potential problems, (2) planning information collection, (3) product design, (4) design validation, (5) product revision, (6) product trial. Learner’s worksheet produced in this study is in accordance with the needs of students and teachers. The subjects in this study were fourth grade students at SDN 33 South Bengkulu. The instruments used were questionnaires and interview guidelines for needs analysis, expert validation sheets to test Learner’s worksheet validation and teacher and student response questionnaires to test the practicality of Learner’s worksheet. The results showed that the Learner’s worksheet developed was valid and feasible to use. This is shown from the analysis of the percentage of expert validation results that are in the